2019
DOI: 10.3382/ps/pey381
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and genotype-environment interactions for growth curve parameters in meat-type quail fed different threonine:lysine ratios from hatching to 21 d of age

Abstract: The aim of the present study was to estimate heritabilities and evaluate the existence of genotype-environment interactions for growth curve parameters in quail fed diets containing different threonine:lysine ratios. A total of 4,441 body weight information from two genetic quail groups (LF1 and LF2) fed diets containing 0.66%, 0.71%, 0.76%, 0.81%, and 0.86% threonine:lysine ratios from hatching to 21 d of age were evaluated. From 22 to 35 d of age, quail received a single diet. The Gompertz model was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…Heritabilities for BW at 6 and 8 weeks of age were estimated at 0.46 and 0.56, respectively (Table 2). Consistent with the findings in the current study, many researchers found high heritabilities (0.40-0.69) for both traits (Akbaş and Yaylak, 2000;Narinç et al, 2010b;Sezer 2007;Taraco et al, 2019;Sarı et al, 2011). The estimates of heritability for the Gompertz model parameter β 0 (0.17), β 1 (0.27), β 2 (0.26), and live weight (0.26) and age (0.19) at an inflection point of growth function were close to those reported in a previously published study in Japanese quail (Akbaş and Yaylak, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Heritabilities for BW at 6 and 8 weeks of age were estimated at 0.46 and 0.56, respectively (Table 2). Consistent with the findings in the current study, many researchers found high heritabilities (0.40-0.69) for both traits (Akbaş and Yaylak, 2000;Narinç et al, 2010b;Sezer 2007;Taraco et al, 2019;Sarı et al, 2011). The estimates of heritability for the Gompertz model parameter β 0 (0.17), β 1 (0.27), β 2 (0.26), and live weight (0.26) and age (0.19) at an inflection point of growth function were close to those reported in a previously published study in Japanese quail (Akbaş and Yaylak, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…The heritability estimates for body weight at 5 and 6 weeks were 0.59 and 0.61, respectively (Table 2). Numerous researchers have observed high heritability estimates (0.46-0.69) for both characteristics [10,18,38,39], which are consistent with the findings of this study. As mentioned previously, there are few studies on the genetics of feed efficiency in Japanese quail, and these studies only assessed feed intake and feed conversion characteristics at short time intervals.…”
Section: Discussionsupporting
confidence: 92%
“…There was no significant dietary effect on any growth curve parameter in their study [31]. Taroco et al [32] investigated the genotype-environment interaction effects of adding five different levels of threonine:lysine to Japanese quail diets in terms of Gompertz model parameters. Researchers reported that this application had significant effects on the heritability and phenotypic values of the asymptotic weight parameter and inflection point age characteristics of the Gompertz model.…”
Section: Discussionmentioning
confidence: 94%